4v-18=6(v-4)

Simple and best practice solution for 4v-18=6(v-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4v-18=6(v-4) equation:


Simplifying
4v + -18 = 6(v + -4)

Reorder the terms:
-18 + 4v = 6(v + -4)

Reorder the terms:
-18 + 4v = 6(-4 + v)
-18 + 4v = (-4 * 6 + v * 6)
-18 + 4v = (-24 + 6v)

Solving
-18 + 4v = -24 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-18 + 4v + -6v = -24 + 6v + -6v

Combine like terms: 4v + -6v = -2v
-18 + -2v = -24 + 6v + -6v

Combine like terms: 6v + -6v = 0
-18 + -2v = -24 + 0
-18 + -2v = -24

Add '18' to each side of the equation.
-18 + 18 + -2v = -24 + 18

Combine like terms: -18 + 18 = 0
0 + -2v = -24 + 18
-2v = -24 + 18

Combine like terms: -24 + 18 = -6
-2v = -6

Divide each side by '-2'.
v = 3

Simplifying
v = 3

See similar equations:

| -5a-2=3(a-6) | | 760-50h=0 | | -9.7(1.7x-5)+6= | | .16x+.8(x-4)=.01(3x-2) | | 3+2x=2(2x+2)-3(x-3) | | 3(2x-6)=4(x+2) | | 2w+2(4x-7)=86 | | 7m+12/8=2m-1/3 | | 4p^2=-9p-2 | | 3x-1+x+x=6.4 | | 3(2x-6)=-4(x-2) | | c^2=33 | | -z-3.2=-22.8+3z | | 0.05(342-x)+0.07x=72 | | 2x+2(x-1)=2x-16+3x | | 3(2x-4)=-4(x-2) | | 16x^2=144-9y^2 | | (10m)/(5m) | | 4x=-2(3x-5) | | z^3-3iz^2-3z+i+1=0 | | 10m/5m | | -9x+12x-10-4x-2x=47 | | 0.3x+0.4=0.9x-1.4 | | 3x^2-8k=16 | | 2y-10x^2+4=0 | | 8+3m-3=9m+12-5m | | 4t-6=12t-24+18 | | 78+3x=10x-97 | | 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 |

Equations solver categories